2019
DOI: 10.1038/s41467-019-12718-0
|View full text |Cite
|
Sign up to set email alerts
|

Unique structure and function of viral rhodopsins

Abstract: Recently, two groups of rhodopsin genes were identified in large double-stranded DNA viruses. The structure and function of viral rhodopsins are unknown. We present functional characterization and high-resolution structure of an Organic Lake Phycodnavirus rhodopsin II (OLPVRII) of group 2. It forms a pentamer, with a symmetrical, bottle-like central channel with the narrow vestibule in the cytoplasmic part covered by a ring of 5 arginines, whereas 5 phenylalanines form a hydrophobic barrier in its exit. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 80 publications
0
39
0
Order By: Relevance
“…Among the members of the rhodopsin family are light-driven proton, anion and cation pumps, light-gated anion and cation channels, and photoreceptors (3,5,14,15). Genomic and metagenomic studies dramatically expanded the world of rhodopsin sequences, some of which were found in unexpected organisms and habitats: for example, sodium-pumping rhodopsins in Flavobacteria (16,17) and the rhodopsins from giant viruses (18)(19)(20). The widely spread presence and importance of pR-based phototrophy in the marine environment (21) were identified.…”
mentioning
confidence: 99%
“…Among the members of the rhodopsin family are light-driven proton, anion and cation pumps, light-gated anion and cation channels, and photoreceptors (3,5,14,15). Genomic and metagenomic studies dramatically expanded the world of rhodopsin sequences, some of which were found in unexpected organisms and habitats: for example, sodium-pumping rhodopsins in Flavobacteria (16,17) and the rhodopsins from giant viruses (18)(19)(20). The widely spread presence and importance of pR-based phototrophy in the marine environment (21) were identified.…”
mentioning
confidence: 99%
“…One of the best examples of the biotechnological harvest of metagenomics has been the retrieval of a vast diversity of retinal proteins (rhodopsins) [56][57][58] critical for the development of optogenetics, a technology with remarkable potential in neurobiology and medicine [59,60]. The photic zone of the ocean is the quintessential habitat to screen for the diversity of rhodopsins and already many have been retrieved by SR assembly metagenomics [61,62]. Remarkably, the largest numbers of rhodopsins (>200 amino acids, clustered at 90 % amino acid identity) were found in the individual LRa (330 rhodopsin genes/Gb assembled) ( Figure 3A).…”
Section: Recovery Of Novel Genesmentioning
confidence: 99%
“…Preliminary data shows that the presented approach works well also for larger K 10 (40 TM helices) and smaller c 13 (26 TM helices) rings (data not shown). We believe that it can be used for assembly of other protein complexes with encapsulated lipids such as the multidrug exporter AcrB (Qiu et al, 2018) or oligomeric light-driven pumps, microbial rhodopsins (Gushchin and Gordeliy, 2018; Bratanov et al, 2019; Kovalev et al, 2019) as well. As lipids are often critical for correct folding and operation of membrane proteins (Cournia et al, 2015; Hedger and Sansom, 2016; Gupta et al, 2017), reproducing their correct positions in simulations is of utmost importance.…”
Section: Resultsmentioning
confidence: 99%